Anabolic androgen steroids cardiovascular impact. Literature review - Balcer, Bartosz; Natalia Dolata (Quality in Sport, 2024)
Introduction and Purpose: The use of anabolic steroids is widespread. They can be administered either therapeutically or by individuals looking to enhance their athletic performance. This review aims to summarize the scientific understanding regarding the link between the use of AASs and the incidence of cardiovascular complications. Materials and methods The literature available in PubMed and Google Scholar databases was reviewed using the keywords. Description of the state of knowledge: A lot of studies suggest that AASs can be harmful to the cardiovascular system. It has a wide range of long-term and often irreversible consequences. AASs cause myocardial hypertrophy which results in systolic and diastolic disfunction. They disrupt lipid metabolism, act as vasoconstrictors, and promote the calcification of blood vessel walls, thereby increasing the risk of heart attack and stroke. By promoting blood clotting, they increase the incidence of pulmonary embolism, deep vein thrombosis, and cerebral venous sinus thrombosis. The effect on the occurrence of hypertension is not definitively proven. However, a very dangerous consequence of using anabolic steroids is the increased risk of life-threatening arrhythmias -especially ventricular arrhythmias- which can lead to sudden cardiac death. Conclusion: The use of anabolic steroids increases the risk of arrhythmias, heart attacks, and thromboembolic complications, ultimately leading to a higher risk of sudden cardiac death. However, the cause-and-effect relationship is not always clearly captured, and further research is necessary to draw appropriate conclusions.